2001
DOI: 10.1177/003172170108200805
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Success?

Abstract: VER the past 30 years educational researchers have learned some important lessons about the impact of school size. 1 Gradually, a picture of the American high school of the future has emerged from this research, and it suggests that the high school of the future will be much smaller than it is today. Indeed, the most recent research study I can find that advocates the current concept of the high school was published in 1971. 2 Essentially all the data since then point to the superiority-in school climate, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The modern continuation school provides several options to students outside of vocational education; students can use their tenure at most continuation schools to make-up deficient academic credits, return to a mainstream school, or to earn a high school diploma from the continuation high school (Gates and Stuht 2006). Although the origins of continuation high schools in California differ from other public alternative programs, having begun at a much earlier date in 1919, they are generally subsumed within the alternative school movement (Deal and Nolan 1978;Lange 1998;Gregory 2001;Lange and Sletten 2002;California Department of Education 2006;Lehr, Tan, and Ysseldyke 2009).…”
Section: Continuation High Schools and Alternative Educationmentioning
confidence: 99%
“…The modern continuation school provides several options to students outside of vocational education; students can use their tenure at most continuation schools to make-up deficient academic credits, return to a mainstream school, or to earn a high school diploma from the continuation high school (Gates and Stuht 2006). Although the origins of continuation high schools in California differ from other public alternative programs, having begun at a much earlier date in 1919, they are generally subsumed within the alternative school movement (Deal and Nolan 1978;Lange 1998;Gregory 2001;Lange and Sletten 2002;California Department of Education 2006;Lehr, Tan, and Ysseldyke 2009).…”
Section: Continuation High Schools and Alternative Educationmentioning
confidence: 99%
“…Here, I focus on the issue of unequal resources, which compromises equitable access to learning opportunities. Gregory (2001) reported that alternatives are routinely placed in "substandard facilities," based on studying "alternative schools in more than half of the states for more than 25 years" (p. 579). It is not uncommon for alternatives to be located in peripheral (e.g., basements) or "temporary" (i.e., portable building) spaces (e.g., Kelly, 1993, p. 80;Schutz & Harris, 2001, p. 51; see Kelly, 2000, pp. 96-99 on the "politics of location").…”
Section: The Context Of Maldistribution: Struggles For Equitable Reso...mentioning
confidence: 99%
“…Equitable resources are necessary to offer quality alternatives. Gregory (2001) highlighted the inspiring example of Open School in Jefferson County, Colorado, which "negotiated with the district to reclaim its fair share of infrastructure resources" to cover costs of personalization and its experiential curriculum, including extended trips around the world (p. 580).…”
Section: The Context Of Maldistribution: Struggles For Equitable Reso...mentioning
confidence: 99%